Evaluasi Koleksi Bahan Pustaka di Perpustakaan (Jurnal Adabiya, 2020)
Evaluation of library collections is a mandatory activity that must be done librarian to keep the qualityof collection and existence of the library. The purpose of this study is to explain the efforts made librarians infulfilling the needs of userinformation through collection evaluation in library with ALA standar. This research usesdescriptive qualitative approach using literature study. The results showed that evaluation of library collectioncan be done with two methods. First, centralized method on a collection; by checking lists, bibliographies, andcatalogs, expert opinions (subject specialist), and comparisons of statistical data. Second, the comparison methodwith various collection standards; by analyzing circulation studies, user opinions, analysis of library borrowingbetween libraries, citation studies, on-site usage studies (reading room), and availability of shelf collections.Librarians must evaluate collections periodically to keep the collection quality as user needs.
Keywords: Library; evaluation; library collection; collection management